Book Reviews (Journal of Finance, 1994)
Book reviewed in this article: Free Markets, Finance, Ethics, and Law . By LARRY ALAN BEAR and RITA MALDONADO‐BEAR. Englewood Cliffs, N.J.: Prentice‐Hall, 1994. Pp. xiii + 434. Investment Under Uncertainty . By AVINASH K. DIXIT and ROBERT S. PINDYCK. Princeton, N.J.: Princeton University Press, 1994. Pp. xiv + 468. Financial Institutions and Markets . By MEIR KOHN. New York, New York: McGraw‐Hill, Inc., 1994. Pp. xxvii + 868. Anatomy of a Merger: The Causes and Effects of Mergers and Acquisitions . By ALEXANDRA M. POST. Englewood Cliffs, N.J.: Prentice‐Hall, 1994. Pp. xii + 258. The Law and Insider Trading: In Search of a Level Playing Field . By ELIZABETH SZOCKYI. Buffalo: William S. Hein & Co., 1993. Pp. x + 151.